2021
DOI: 10.1186/s12936-021-03857-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with malaria vaccine uptake in Sunyani Municipality, Ghana

Abstract: Background Malaria continues to be a major disease of public health concern affecting several million people worldwide. The World Health Organization (WHO) started a pilot study on a malaria vaccine (RTS,S) in Ghana and two other countries in 2019. This study aimed at assessing the factors associated with uptake of the vaccine in the Sunyani Municipality of Ghana. Methods The study was a cross-sectional study employing a quantitative approach. Stra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 8 publications
2
21
0
Order By: Relevance
“…When the children immunization statuses were confirmed using vaccination cards and mothers recall method, it came to light through the study findings that, fully immunized coverage was high (94%) among the study participants. This figure is in line with WHO's Global Vaccine Action Plan which proposes that countries attain about 90 percent and districts attain about 80 percent fully immunized children by the year 2020 [16]. The findings from this study showed a comparatively similar results to a study in Sunyani [16] in the Bono Region of Ghana, which indicated that uptake of RTS,S first dose was 94.1 percent.…”
Section: Level Of Uptake Of Rtsssupporting
confidence: 89%
See 2 more Smart Citations
“…When the children immunization statuses were confirmed using vaccination cards and mothers recall method, it came to light through the study findings that, fully immunized coverage was high (94%) among the study participants. This figure is in line with WHO's Global Vaccine Action Plan which proposes that countries attain about 90 percent and districts attain about 80 percent fully immunized children by the year 2020 [16]. The findings from this study showed a comparatively similar results to a study in Sunyani [16] in the Bono Region of Ghana, which indicated that uptake of RTS,S first dose was 94.1 percent.…”
Section: Level Of Uptake Of Rtsssupporting
confidence: 89%
“…This figure is in line with WHO's Global Vaccine Action Plan which proposes that countries attain about 90 percent and districts attain about 80 percent fully immunized children by the year 2020 [16]. The findings from this study showed a comparatively similar results to a study in Sunyani [16] in the Bono Region of Ghana, which indicated that uptake of RTS,S first dose was 94.1 percent. Nonetheless, this figure declined to 90.6 percent for RTS,S second dose, and 78.1 percent for RTS,S third dose.…”
Section: Level Of Uptake Of Rtsssupporting
confidence: 89%
See 1 more Smart Citation
“…Our analysis included 11 studies with a total sample size of 14, 666 participants. A majority (n = 8) [19][20][21][22][23][24][25][26] of the studies were published on or after 2018, while the remaining (n = 3) [16][17][18] studies were published before 2018. The most recently published study wasin 2022, [23] and the oldest study was published in 2014 [16].…”
Section: Characteristics Of Studies Included In This Reviewmentioning
confidence: 99%
“…Development of an antimalarial vaccine will be important for regional malaria elimination and future eradication effort. Malaria vaccine policy is a global effort and the vaccine has already been applied to a high number of children in Ghana, Kenya, and Malawi [14][15][16].…”
Section: Introductionmentioning
confidence: 99%